2004
DOI: 10.1016/j.jmhg.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and gender in the physician-patient interaction

Abstract: The goal of this review is to show that physician-patient interactions differ in the degree of dominance asymmetry between the physician and the patient, that physician's dominance behavior is related to negative patient outcomes, and that physician gender affects how physician dominance is perceived by patients. The article provides (1) an overview of existing findings on dominance in the physician-patient interaction, (2) a summary of gender differences in dominance with an emphasis on the physician-patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Moreover, whether the doctor is a man or a woman has significant bearing when it comes to (non‐)dominating behaviour within the doctor–patient relationship. Female doctors adopt a less dominant interaction style with their patients than do male doctors, which is related to better adherence and positive patient health outcomes 16,17 . In summary, recognition of gender‐related factors in doctor–patient communication (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whether the doctor is a man or a woman has significant bearing when it comes to (non‐)dominating behaviour within the doctor–patient relationship. Female doctors adopt a less dominant interaction style with their patients than do male doctors, which is related to better adherence and positive patient health outcomes 16,17 . In summary, recognition of gender‐related factors in doctor–patient communication (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The latter area of process has been subject to a great deal of research across the helping professions and various core skills have been identified. Recent work in this area has included the development of the REDE model of healthcare communication (Relationship: Establishment, Development and Engagement) (Windover et al, 2014). The checklist based on this includes skills such as reflective listening, empathy and collaboration.…”
Section: Towards a Model Of Effective Forensic Clinical Interviewingmentioning
confidence: 99%
“…In another research, Schmidmast (2004) conducted a study on physicianpatient interactions to find the degree of dominance asymmetry between physicians and patients. He concluded that female physicians adopted a less dominant interaction style with their patients than male physicians did by including their patients in decision making, eliciting their patients' concerns, experiences, norms, and values, asking for their patients' opinion, not interrupting their patients and treating their patients with respect.…”
Section: Review Of Literaturementioning
confidence: 99%